A Managerial Perspective of Corporate Social And Environmental Responsibility (CSER) Reporting: Evidence from a Developing Country - Hossain, Md. Moazzem; Rowe, Anna; Quaddus, Mohammed (Emerald, 2013)
This extensive engagement based research towards an understanding of corporate social andenvironmental responsibility (CSER) reporting is aimed at exploring the emergingphenomenon of CSER within a developing country context by seeking the views of twentysenior managers of listed companies in Bangladesh. This study is part of a larger project thatfollows a qualitative field research approach using semi-structured interviews. Observationsand local working experience provided rich sources of data. Thus, to understand CSERreporting phenomenon, particularly motivations, decision-makers engagement and futureprospect of CSER reporting in Bangladesh, constructivist ontology and interpretivistepistemology research methodology have been chosen. This paper extends the utilisation of avariety of social system-based theoretical concepts such as legitimacy theory, stakeholdertheory and institutional theory that have been widely approached by accounting researchers inCSER sustainability studies. Findings reveal key enablers for CSER reporting, whichinclude groups such as: board of directors, regulatory authority, external pressure group andsocio-economic contextual factors such as poverty alleviation. Whilst stakeholder engagementprocess is still in its infancy in Bangladesh, senior managers are optimistic about the futureprospect of CSER reporting. Awareness among the stakeholders, as well as senior managerialattitudes, and the role of regulatory authorities may have vital sway on the diffusion of CSER.The field research findings contribute to the body of knowledge in the literature, especially inthe context of developing countries. It will be of great value to researchers and practitionersseeking to gain a better understanding of CSER reporting in various social-systems basedtheoretical aspects.